Benefits, challenges and critical factors of success for Zero Waste: A systematic literature review. (September 2017) - Pietzsch, Natália; Ribeiro, José Luis Duarte; de Medeiros, Janine Fleith
Highlights: Implementation of ZW requires a holistic point of view. ZW encompasses waste prevention as well as behavioral changes. Critical factors for implementation can be organized in governance and operationalization. Economic growth, measurement mechanisms and consumer behavior inhibit ZW. Abstract: Considering the growing concern with solid wastes problems and the pressing need for a holistic approach to their management, this study developed a literature review about the subject "Zero Waste". To that end, a systematic literature review was executed, through which 102 published articles were analyzed with the aim to, initially, comprehend the concept of Zero Waste, and, then, map its benefits, challenges, and critical success factors. The results show that scholars have not reached a consensus regarding the concept of ZW. While some studies fully address this philosophy, other studies are based on just one or on some of its topics. The benefits were grouped and organized into four dimensions: benefits to the community, financial-economic benefits, benefits to the environment and benefits to the industry and stakeholders. As to the challenges, barriers were identified both in the macro environment (mainly political and cultural) and in the meso and micro environments (stakeholders, industries, and municipalities). The analysis of the articles enabled listing critical success factors, supported by a set of activities that must be carried out. Regarding future studies, it is worth noting that more empirical studies about ZW implementation are necessary, particularly with regard to educational practices designed to promote changes in user behavior.